The Oscillatory of Linear Conformable Fractional Differential Equations of Kamenev Type - Hui Liu; Run Xu (Discrete Dynamics in Nature and Society)
In this paper, the oscillatory of the Kamenev-type linear conformable fractional differential equations in the form of ptyα+1tα+yα+1t+qtyt=0 is studied, where t≥t0 and 0<α≤1. By employing a generalized Riccati transformation technique and integral average method, we obtain some oscillation criteria for the equation. We also give some examples to illustrate the significance of our results.